Effects of toe-in angles on knee biomechanics in cycling of patients with medial knee osteoarthritis - Gardner, Jacob K.; Zhang, Songning; Liu, Hairui; Klipple, Gary; Stewart, Candice; Milner, Clare E.; Asif, Irfan M. (Clinical biomechanics (Bristol), 2015)
Cycling is commonly prescribed for knee osteoarthritis, but previous literature on biomechanics during cycling and the effects of acute intervention on osteoarthritis patients does not exist. Due to their altered knee kinematics, osteoarthritis patients may be at greater risk of osteoarthritis progression or other knee injuries during cycling. This study investigated the effects of reduced foot progression (toe-in) angles on knee joint biomechanics in subjects with medial compartment knee osteoarthritis. Thirteen osteoarthritis and 11 healthy subjects participated in this study. A motion analysis system and custom instrumented pedal was used to collect 5 pedal cycles of kinematic and kinetic data in 1 neutral and 2 toe-in conditions (5° and 10°) at 60 RPM and 80W. For peak knee adduction angle, there was a 61% (2.7°) and a 73% (3.2°) decrease in the 5° and 10° toe-in conditions compared to neutral in the osteoarthritis group and a 77% (1.7°) and 109% (2.4°) decrease in the healthy group for the 5° and 10° conditions, respectively. This finding was not accompanied by a decrease in pain or peak knee abduction moment. A simple linear regression showed a positive correlation between Kelgren–Lawrence score and both peak knee adduction angle and abduction moment. For individuals who cycle with increased knee adduction angles, decreasing the foot progression angle may be beneficial for reducing the risk of overuse knee injuries during cycling by resulting in a frontal plane knee alignment closer to a neutral position. •We examined lower extremity biomechanical differences in toe-in and neutral cycling.•Knee adduction angle decreased with toe-in cycling but not pain and knee moment.•Increasing toe-in angle may be beneficial in correcting knee malalignment.